Parameterization of the turbulent diffusion coefficient of industrial emissions; Методология проектирования молодежного научно-инновационного пространства как основа подготовки современного инженера - Pokrovskaya E. A. Elena Aleksandrovna (Integrity of traditions and innovations as the basis for the development of modern engineering science, 2014)
Заглавие с экрана